Assessment of functional capacity and quality of life of middle-aged and elderly women registered in the Family Health Strategy in Conselheiro Lafaiete-MG (Research, Society and Development, 2022)
The functional capacity is related to physical, cognitive and emotional aspects of individuals and in the aging process, reductions in its levels can be observed, due to the decrease in muscle strength, balance, mobility and gait. Therefore, the current study evaluates the functional capacity and quality of life of elderly and middle-aged women in the city of Conselheiro Lafaiete-MG registered in the Family Health Strategy (ESF). Cross-sectional study, conducted with 26 women (n=18) elderly and (n=8) middle-aged, who underwent the 30-s chair-stand test (30s-CST), timed up and go (TUG), six-minute walk test (6MWT) and answered the SF-36 quality of life questionnaire. The results indicate that in 30s-CST and TUG there was no significant difference between intra group participants; in the 6MWT, middle-aged women walked a shorter distance than expected for their age; in the SF-36, when the middle-aged and elderly groups were compared, the domain functional capacity, limitation due to physical aspects, pain, social aspects, limitation due to emotional aspects and mental health of the elderly women had a worse score. It is concluded that the functional capacity is interconnected with the quality of life, whose reductions in strength, agility and balance are directly reflected in the worsening of the quality of life of these women.